Pediatric anterior thoracic wall reconstruction: a successful case of extensive resection and repair - Izchel Valdez García; Alfa Guadalupe Barraza Tinajero; Nayely Carrillo Ibarra; Sofia Brenes Guzmán (SpringerOpen, 2024)
Abstract Background Thoracic tumors are a challenge for pediatric surgeons. They comprise a heterogeneous group of neoplasms classified based on histological variety, location, presentation, biological behavior, treatment response, and prognosis. Primary tumors of the thoracic wall in children and adolescents are sporadic, accounting for only 1-2% of all pediatric thoracic neoplasms, with two-thirds of them being malignant. Case presentation We present the case of a 16-year-old male patient with osteoblastic osteosarcoma localized in the right anterior rib cage. The patient underwent extensive tumor resection using titanium bars. Conclusion Thoracic reconstruction following extensive resection in pediatric cancer patients has been underexplored and poorly described. Nevertheless, it has been demonstrated to be feasible, particularly considering the 5-year survival rate of 60% following tumor resection. This approach helps prevent anatomical and physiological complications that may arise without reconstruction. We report a successful single-stage resection and thoracic reconstruction case in a pediatric patient. This case underscores the importance of considering reconstruction in patients with thoracic tumors, as it can contribute to improving prognosis and preventing associated complications.